1982
DOI: 10.1051/parasite/1982576527
|View full text |Cite
|
Sign up to set email alerts
|

Typage enzymatique de onze souches de Leishmania isolées, en Italie continentale, à partir de formes viscérales murines, canines et vulpines

Abstract: A nnales de Parasitologie (Paris ; 1982, t. 57, n° 6, pp. 527

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Strain identification is a basic investigation useful for the knowledge of Leishmania foci and the understanding of the clinical outcome of leishmaniasis. The ecoepidemiological studies of leishmaniasis have made real progress thanks to the isoenzyme identification [20][21][22][23][24]. Identical clinical lesions may occur due to different species of Leishmania, which stresses the high interest of isoenzyme identification of the strains occurring in the area of Annaba [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain identification is a basic investigation useful for the knowledge of Leishmania foci and the understanding of the clinical outcome of leishmaniasis. The ecoepidemiological studies of leishmaniasis have made real progress thanks to the isoenzyme identification [20][21][22][23][24]. Identical clinical lesions may occur due to different species of Leishmania, which stresses the high interest of isoenzyme identification of the strains occurring in the area of Annaba [25].…”
Section: Discussionmentioning
confidence: 99%
“…In Tunisia, Kallel et al (2005) L. infantum MON-1 is the principal agent of Mediterranean VL [38]. However, it was isolated in cases of SCL in Algeria [3,32,39], in Tunisia [40], in France [25],in Spain [29], in Greece [31], in Italy [23] and in Portugal [41]. It has been described in Tunisia first in SCL by Aoun et al (2000), with two strains against six of L. infantum MON-24.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from skin biopsy samples (PCR template preparation kit, Roche, Germany) and analysed by real-time TaqMan ' PCR for Leishmania DNA detection (Rolão et al, 2004). The PCR primers (forward, 5'-GGTTAGCCGATGGTGGTCTT-3', reverse, 5'-GCTATATCATATGTCCAAGCACTTACCT-3') and the TaqMan ® internal probe (5'-ACCACCTAAGGTCAACCC-3') (Applied Biosystems, Foster City, CA, USA) were designed from a kDNA minicircle sequence of a mediterrean region isolate of L. infantum (Genebank A/N AF169140 (Rioux et al, 1968), Italy (Gramicia et al, 1982), Portugal (Abranches et al, 1984) and Spain (Fisa et al, 1999), and black rats in Italy (Gradoni et al, 1983) and Spain (Morillas-Márquez et al, 1985), which have been considered wild reservoirs. Cats in Portugal (Durão et al, 1994), Spain (Hervas et al, 1999), France (Ozon et al, 1998) and Italy (Poli et al, 2002;Pennisi et al, 2004), and a wolf in Portugal (Rebelo, personal communication) have also been found parasitized and generally considered as accidental hosts.…”
mentioning
confidence: 99%
“…gênero Acomys e Rattus com lesões dermatológicas compatíveis com LT. Infelizmente o parasito ainda não foi isolado, sendo identificado apenas o gênero Leishmania (HOOGSTRAAL et al, 1963;PETROVIC et al, 1975;BETTINI et al, 1980;LAINSON et al, 1981;GRAMICCIA et al, 1982;AZAB et al, 1984;IBRAHIM et al, 1992;KERR et al, 1995).…”
Section: Referencial Teóricounclassified